Assessing invasion process through pathway and vector analysis: case of Saltcedar (Tamarix spp.) - Natale, Evangelina Sandra (2012)
Biological invasions are one of the most pervasive environmental threats to native ecosystems worldwide. The spontaneous spread of saltcedar is a particular threat to biodiversity conservation in arid and semiarid environments. In Argentina, three species belonging to this genus have been recognized as invaders. The aim of the present study was to identify main dispersal vectors and pathways to refine risk analysis and increase our ability to predict new areas at risk of Tamarix establishment. We surveyed and categorized 223 populations, 39% as invasive, 26% as established, 21% as contained and 14% as detected in nature. Dispersion of saltcedar was found to be associated with watercourses and human-driven disturbances; in addition roads were found to be relevant for the introduction of propagules in new environments. Considering the potential impact of saltcedar invasion and that it is an easily wind-dispersed invasive, it is necessary to implement strategies to monitor dispersal pathways and take actions to eliminate invasion foci, particularly in vulnerable and high- conservation value areas.